1998
DOI: 10.1097/00006454-199807000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, presenting features, risk factors and significance of late onset septicemia in very low birth weight infants

Abstract: Late onset septicemia is common in very low birth weight infants, and the rate is inversely proportional to gestational age and birth weight. Septicemia is more common in males and those with low initial serum IgG values. A set of clinical signs (apnea, bradycardia, etc.) and laboratory values (leukocytosis, immature white blood cells and neutropenia) increase the probability of late onset sepsis, but they have poor positive predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
246
4
12

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(280 citation statements)
references
References 16 publications
18
246
4
12
Order By: Relevance
“…That study, however, included both preterm VLBW and term newborns with sepsis, most of which were of early-onset and not cultureproven. Even using the reference ranges as proposed by Manroe et al 8 for mature infants, Fanaroff et al 13 also reported only an 8% incidence neutropenia (ANC <1500/mm 3 ) in infants with late-onset sepsis. In their large multicentric trial, more than twothirds of cases were caused by Gram-negative organisms.…”
Section: Discussionmentioning
confidence: 99%
“…That study, however, included both preterm VLBW and term newborns with sepsis, most of which were of early-onset and not cultureproven. Even using the reference ranges as proposed by Manroe et al 8 for mature infants, Fanaroff et al 13 also reported only an 8% incidence neutropenia (ANC <1500/mm 3 ) in infants with late-onset sepsis. In their large multicentric trial, more than twothirds of cases were caused by Gram-negative organisms.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Infection is a major cause of mortality and morbidity among VLBW infants (birth weight <1500 g). 3,4 Systemic candidiasis has become increasingly important as a cause of infection in VLBW infants. [5][6][7] Neonatal candidemia occurs in 1.6 to 9% of VLBW infants 1,2 and 4 to 15% in extremely low birth weight infants (ELBW; birth weight <1000 g), with the 30-day mortality approaching 40%.…”
Section: Introductionmentioning
confidence: 99%
“…In early-onset sepsis, criteria for diagnosis are relatively well established, 1 but such criteria cannot be used with LNS because of known differences in risk factors, clinical features, and causative pathogens. 2 Few clinical scoring methods for the prediction of LNS have been developed, and they were mainly from the data of the neonates who had been worked-up as suspected sepsis. [3][4][5] The objectives of this study were to develop a practical, clinical prediction-scoring model for the diagnosis of LNS, and to validate the diagnostic performance of the model.…”
Section: Introductionmentioning
confidence: 99%